The Effect of Transformational Leadership and Management Control System on Organizational Performance through Organizational Culture as an Intervening Variable - Sentoso, Antony; Shofiah, Siti; Purwianti, Lily (Almana : Jurnal Manajemen dan Bisnis, 2025)
Public sector organizations are currently experiencing rapid development and change. As one of the public sector entities, the Riau Islands Provincial Government faces various challenges in realizing its vision and mission. In accordance with the 2021-2026 Regional Medium-Term Development Plan (RPJMD) with the vision of 'Realizing a Prosperous, Competitive and Cultured Riau Islands', one of whose missions is to Implement Clean, Open and Service-Oriented Governance. Various challenges in achieving this vision require serious attention, especially in the aspects of Transformational Leadership and management control systems applied to all OPDs in the Riau Islands Province. The purpose of this study is to see the effect of Transformational Leadership and management control systems on Organizational Performance with Organizational culture as an intervening variable. This type of research is Quantitative. The number of samples in this study was 318 respondents in the OPD of the Riau Islands Province. The researcher used the help of the SMART PLS software program, with an approach in modeling using the Structural Equation Model (SEM) analysis. The results of this study all research hypotheses were accepted and Organizational Culture was an intervening variable between Transformational Leadership on Organizational Performance and Management Control System on Organizational Performance.